Strategic Dependence and the Assessment of Fraud Risk: A Laboratory Study - Bloomfield, Robert J. (The Accounting Review, 1997)
[This study shows that subjects acting as auditors in laboratory experiments have more trouble assessing fraud risk when their optimal strategies are highly sensitive to those assessments. Interestingly, risk assessment is particularly difficult when the auditor faces high legal liability for audit failure and audits a firm with strong internal controls. The results have practical implications for auditors, who must assess fraud risk accurately in order to be cost competitive while avoiding audit failures that might result in legal liability. The results also have implications for auditing research, because they indicate settings in which traditional equilibrium analyses (which assume accurate fraud risk assessment) are likely to have low predictive power.]